2022
DOI: 10.32526/ennrj/20/202200038
|View full text |Cite
|
Sign up to set email alerts
|

Color Removal of Pulp and Paper Mill Wastewater Using Residual Eucalyptus Wood

Abstract: This study investigated the color removal efficiency of pulp and paper mill wastewater using residual eucalyptus wood as a method to minimize the solid wastes generated from pulp and paper processes. The activated carbon used in this study as the color adsorbent was produced from residual eucalyptus wood. The carbon was activated with phosphoric acid and carbonized in a furnace at 500°C for 60 min. Effects of types and amounts of activated carbon on color removal efficiency were evaluated. Three types of solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…94 An experiment using activated carbon derived from residual eucalyptus wood as an adsorbent for the removal of color from P&P mill wastewater demonstrated that, despite the high surface area of the adsorbent, the cost of 7 g of adsorbent to treat the wastewater was not competitive enough. 95 As another inexpensive and environmentally friendly adsorbent, activated carbon can be produced by pyrolysis of mixed plastic waste, and its application to waste plastic management and wastewater treatment may solve both problems simultaneously. Based on the optimization, 1.25 g of adsorbent dose, pH of 8, contact time of 7 h, agitation speed of 184 rpm, and temperature of 40 °C, 98.46% of color and 94.25% of lignin were eliminated.…”
Section: Reverse Osmosis (Ro)mentioning
confidence: 99%
“…94 An experiment using activated carbon derived from residual eucalyptus wood as an adsorbent for the removal of color from P&P mill wastewater demonstrated that, despite the high surface area of the adsorbent, the cost of 7 g of adsorbent to treat the wastewater was not competitive enough. 95 As another inexpensive and environmentally friendly adsorbent, activated carbon can be produced by pyrolysis of mixed plastic waste, and its application to waste plastic management and wastewater treatment may solve both problems simultaneously. Based on the optimization, 1.25 g of adsorbent dose, pH of 8, contact time of 7 h, agitation speed of 184 rpm, and temperature of 40 °C, 98.46% of color and 94.25% of lignin were eliminated.…”
Section: Reverse Osmosis (Ro)mentioning
confidence: 99%